Psychology, Performance, and Social Context of Laughter in Azerbaijan Folklore - Garayev, Safa (Journal of History Culture and Art Research, 2020)
Social context often drives the performance of laughter in cultural situations. As a metaphor, laughter provides not only an exchange of integrative information among the community members, but also the enactment of aggressive relations in the society. These characteristics may be seen clearly while observing metaphors related to the performance of laughter in the Azerbaijani socio-cultural environment. In the study of humor, content is usually analyzed but the performance of behavioral cues such as laughter is neglected, although it can shed light on the meaning of the communication. To understand folk behaviors and texts related to the laughter, I argue that special attention needs to be given to behaviors as well as texts communicated in a social situation. This study reveals that the jokes causing laughter are accepted and perceived by the male and female audiences differently. Women’s laughter receives disapproval in the Azerbaijan cultural context regarding sexuality. Men take such laughter to be a threat to their manliness.